2000
DOI: 10.1046/j.1365-2265.2000.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth hormone and IGF‐I in a pregnant woman with Pit‐1 deficiency

Abstract: The respective contributions of pituitary and placental GH to circulating IGF-I in pregnant women have not been well established. We measured the serum concentrations of placental growth hormone (PGH) and IGF-I in a woman with pit-1 deficiency before, during and after pregnancy, resulting in the birth of a healthy child (not pit-1 deficient). Both PGH and IGF-I concentrations were below the assay detection limit before and after pregnancy. During pregnancy, PGH and IGF-I levels increased steadily; the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 21 publications
2
27
1
2
Order By: Relevance
“…PGH was the major determinant of IGF-I concentrations, confirming the strong correlation between both variables in normal and IUGR pregnancies (3,4,10). We have reported that PGH and IGF-I concentrations were within the normal range and were highly correlated in a pregnant woman with absent GH secretion owing to pit-1-deficiency (35). The discrepant relation between BW and PGH (negative) vs. BW and IGF-I (positive) may be explained by the fact that insulin is a second important determinant of IGF-I levels.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…PGH was the major determinant of IGF-I concentrations, confirming the strong correlation between both variables in normal and IUGR pregnancies (3,4,10). We have reported that PGH and IGF-I concentrations were within the normal range and were highly correlated in a pregnant woman with absent GH secretion owing to pit-1-deficiency (35). The discrepant relation between BW and PGH (negative) vs. BW and IGF-I (positive) may be explained by the fact that insulin is a second important determinant of IGF-I levels.…”
Section: Discussionsupporting
confidence: 54%
“…PGH was measured by a twosite immunoradiometric assay, using rhPGH as the standard and two monoclonal antibodies. The detection limit is about 10 pmol/liter; within-and between-assay CV are 3.0 -5.5% and 5.0 -7.9%, respectively (33)(34)(35). IGF-I was measured by RIA after acid ethanol extraction, using rhIGF-I as the standard and a polyclonal antiserum raised in guinea pigs.…”
Section: Assaysmentioning
confidence: 99%
“…In the first trimester, GH-N is still the predominant form of GH in maternal blood, does not cross placental barrier and is not essential to normal gestation development as observed in GH-deficient pregnant patients (35,36). During this period, rising estrogen levels would induce a state of GH resistance as reflected by a significant decline in circulating IGF-1, although a compensatory rise in GH-N levels has not been uniformly observed during this period (37,38).…”
Section: The Somatotrophic Axis During Normal Pregnancymentioning
confidence: 99%
“…3 The description of progressive elevation of serum IGF1 in a pregnant woman with Pit-1 deficiency supports the hypothesis that placental GH is the prime regulator of maternal serum IGF1 during pregnancy. 4 GH deficiency is associated with decreased left ventricular ejection fraction at rest and on effort, decreased diastolic filling at rest, decreased myocardial wall thickness and decreased exercise duration and capacity. The severity of cardiac impairment correlates with the severity of GH deficiency.…”
Section: Discussionmentioning
confidence: 99%